Monetary Policy and Wage-Bargaining in the Eurozone: An Epistemological Break? An Analysis from the Perspective of the ECB - Giovanni Borraccia (London School of Economics and Political Science (LSE), European Institute, 2021)
This paper aims to show how, upon the introduction of EMU both structural and ideological factors have concurred to shape ECB's policy stance to envision no need to maintain an active dialogue with national social partners and a blind faith in their capacity/will to constantly pursue wage moderation in parallel with the ECB's guarantee of price stability. A range of research methods is adopted: game theory is used to unpack the dynamics of coordination between central bank and wage-setters. A brief examination of coalitional configurations within the ECB Governing Council and an extensive qualitative text analysis of presidents' speeches and interviews informs the ultimate elaboration of a grounded theory. I will thus define and progressively identify the occurrence of a drastic post-EMU alteration, an epistemological break, in the relationship between monetary policy and wage-bargaining, with the ECB strongly putting forward the conservative idea of a sharp separation between the two and no necessity for ex ante coordination. Such sharp separation can be seen to have concurred to dangerously expose smaller, institutionally weaker peripheral countries to the challenge of maintaining wage moderation even after EMU accession and with a loosened link to monetary authorities. These internal imbalances have then played a pivotal role in the build-up to the European sovereign debt crisis.
Keywords: 330; Monetary policy; wage-bargaining; Eurozone; ECB